If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-x=-13x+36
We move all terms to the left:
-x-(-13x+36)=0
We add all the numbers together, and all the variables
-1x-(-13x+36)=0
We get rid of parentheses
-1x+13x-36=0
We add all the numbers together, and all the variables
12x-36=0
We move all terms containing x to the left, all other terms to the right
12x=36
x=36/12
x=3
| -9-2y=14 | | 4.4x-4.6=30.6 | | 6.4x=-0.4 | | -8-t=5-t | | p(1.59)=5.07 | | 8^3x=81 | | 3y-9y=-6y | | 5.5x-8.9=24.1 | | g-8=-3 | | -76=3e | | d=123=10 | | 1237895=-1000000x+2000000 | | 3x-5=98 | | a2-7a=0 | | 5.5/20=x/2000 | | 7.2+4k=19.2 | | 7u=4u+3u | | m8+5=14 | | 2b+18=34 | | w-32/3=28/9 | | 3(2y+14)-5y=33 | | 5(x-7)=3x-5 | | 819618=-1000000x+2000000 | | 5.4x-16.4=10.6 | | 4(x-5)+7x=19+x | | 3z-17=73 | | 3x-7=98 | | -5+u/3=0 | | 3z-17=107 | | 6-10n=-10n | | (2)(3.14)(1.5^2)+(2)(3.14)(1.5)(9)=x | | n-65/3=9 |